DINAMIKA KELOMPOK STUDI PADA KELOMPOK TANI PAGUYUBAN BUMI MANDIRI DAN KELOMPOK TANI SRI TANGGULUN DI KABUPATEN SUBANG - Evi Faridah Rostanti Meliyani; Tuhpawana P. Sendjaja; A. Choibar Tridakusumah (Universitas Galuh, 2023)
Organic rice is one of the promising rice farming businesses to provide benefits for farmers. Improving the performance of organic rice farming can be supported by the provision of production facilities and the participation of members of farmer groups. The purpose of this study was to determine the dynamics of organic rice farmer groups. The research method used was a survey, the population in this study was 32 organic rice farmers, Peguyuban Bumi Mandiri Farmers Group and Sri Tanggulun Farmers Group. The data analysis design used in this research is descriptive and quantitative analysis methods. The results showed that in general the condition of group dynamics was in the good category. group cohesiveness obtained the largest average index in the good category. Tension in the group obtained the smallest average index with less category. Tensions within the group in organic rice farmer groups include conflicts within the group and competition with other groups.